Pembuatan Tong Sampah di Kelurahan Babussalam Mandau Bengkalis - Marpaung, Noveri; Hutabarat, Sakti; Ervianto, Edy; Kartika, Nursiti Sari; Manurung, David Pratama; Simanjuntak, Anwar Ribert; Kezia, Deswita; Sulastri, Evi; Sianturi, Gabe Daniel; Simamora, Seltia Ledi Sara; Tampubolon, Cindy Artha Ully; Manurung, Diva Cholis; Ningsih, Septia Warda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Keeping clean is an absolute thing that must be performed for mankind. Maintaining cleanliness is an effort which is made to protect anybody and her/his environment from all kinds of dirt and garbage. This effort can realize and create a comfortable and healthy life as well as good hygienic conditions. However, maintaining cleanliness is not an easy thing to do if it is not applied since early. Therefore, sharing knowledge about the importance of cleanliness from early is very necessary. On the other side, Indonesian people still have bad habits about cleanliness, such as people still littering their environmental at one’s pleasure. This bad habit, certainly, has a fatal effect on human health because it can cause various diseases such as tetanus, staphylococcal food poisoning, salmonellosis and others. These circumstances are not found only in cities, but also in villages. Habit of garbage disposing carelessly almost occurs in all circles of society. Those are not only children, even adults who are highly educated as well, performed the same thing. Based on this masalah, therefore the Kukerta Team of Babussalam in 2022 from University of Riau make trash cans in Babussalam Village whereas these trash cans are placed in vital places, such as head office, the shared park b, and also in the function room of the Babussalam village. By this effort, the Babussalam Kukerta Team hopes that a clean environmental will be created around the Babussalam Village to increase the quality of health from Babussalam people.